Innovative Tests During Control Psychomotor Function by Qualified Handballers - Valeria Tyshchenko (Lesya Ukrainka Volyn National University, 2015)
There are a lot of and a number of studies have been performed as to the importance of facilities use in sportsmen training.  Nowadays, when the amount of training load comes to quite high values, further improvement of sportsmanship in many aspects depends on intensification of the workout process. Skilled application of exercise machines and training devices plays an important role in intensification and improvement of performance during the workout process. The aim of the research is justification the control of training by qualified handballers with special technical devices. The necessity to use facilities during workout sessions in handball has been ascertained. Novel informative testing techniques using flashlight tests have been discussed. Application of test exercises, aimed at evaluation of psychomotor system by qualified handball players of the Ukrainian Super League, has been analyzed.